2019
DOI: 10.2147/cia.s189560
|View full text |Cite
|
Sign up to set email alerts
|

<p>The effects of sociodemographic factors on quality of life among people aged 50 years or older are not unequivocal: comparing SF-12, WHOQOL-BREF, and WHOQOL-OLD</p>

Abstract: ObjectiveThe effects of sociodemographic factors on quality of life in older people differ strongly, possibly due to the fact that different measurement instruments have been used. The main aim of this cross-sectional study is to compare the associations of sex, age, marital status, education, and income with quality of life assessed with the Short-Form Health Survey (SF-12), the World Health Organization Quality of Life Questionnaire-BREF (WHOQOL-BREF), and the World Health Organization Quality of Life Questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
67
4
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 50 publications
19
67
4
9
Order By: Relevance
“…There is a positive relationship between the educational level of individuals and the quality of life according to the results of this study. It means that the education level brings higher quality of life, and this result is consistent with the results of previous studies both in Turkey (Nas, ); Daglar, Bilgic, & Özkan, ) and in other countries (Gobbens & Remmen, ; Ward, ). In their study, Torlak and Yavuzçehre () concluded that the level of quality of life was higher among the individuals whose education level was high even the general education level of the region where the study was conducted was low.…”
Section: Discussionsupporting
confidence: 91%
“…There is a positive relationship between the educational level of individuals and the quality of life according to the results of this study. It means that the education level brings higher quality of life, and this result is consistent with the results of previous studies both in Turkey (Nas, ); Daglar, Bilgic, & Özkan, ) and in other countries (Gobbens & Remmen, ; Ward, ). In their study, Torlak and Yavuzçehre () concluded that the level of quality of life was higher among the individuals whose education level was high even the general education level of the region where the study was conducted was low.…”
Section: Discussionsupporting
confidence: 91%
“…Our study identified that male patients had superior general quality of life indexes including the respective domains in relation to female patients, as also observed in other previous studies from different countries [34,35].…”
Section: Discussionsupporting
confidence: 90%
“…343 Psychology wellbeing outcomes among community-dwelling older adults in later life, as assessed using the Geriatric Depression Scale (GDS-15), Satisfaction with Life Scale (SWLS), Subjective Happiness Scale (SHS), and Spiritual Wellbeing Scale (SWBS). It was anticipated that wellbeing in this sample would be related to the same types of sociodemographic background factors, including poverty, education, and income, as have been found in previous researches in other cultural contexts (George, 2010;Gobbens & Remmen, 2019;Gwozdz & Sousa-Poza, 2010). for Children and Adults.…”
Section: Papadopoulosmentioning
confidence: 61%
“…Moreover, before multiple regression, with the psychosocial domains of four scales as dependent variables and all sociodemographic factors as independent variables was performed, dummies for sex ("1" women and "0" men), marital status ("1" married or cohabiting and "0" otherwise), and frequency of church attendance ("0" weekly church attendance and "1" lack of weekly church attendance) were adopted, as used in other studies (Gobbens & Remmen, 2019). Moreover, effects of age, education, and perceived health status were included in these regression analyses.…”
Section: Discussionmentioning
confidence: 99%